An engineered non-erythropoietic erythropoietin-derived peptide, ARA290, attenuates doxorubicin induced genotoxicity and oxidative stress. (August 2020) - Shokrzadeh, Mohammad; Etebari, Mahmoud; Ghassemi-Barghi, Nasrin
Abstract: Erythropoietin (EPO) applies anti-inflammatory, anti-apoptotic, anti-oxidant and cytoprotective effects besides its hematopoietic action. A nonhematopoietic peptide engineered from EPO, ARA 290, interacts selectively with the innate repair receptor and has similar possessions. ARA290 mediates tissue protection without hematopoietic side-effects of EPO which limit its clinical application. Doxorubicin (DOX) is the broad-spectrum chemotherapeutic agent, but its use is limited by the development of nonspecific toxicity on noncancerous tissues especially in cardiac cells. Mechanisms behind the DOX-induced toxicities are enhanced level of oxidative damage, inflammation and apoptosis. In the present study, we have investigated whether ARA290 acts as a chemoprotective agent modulating the cytotoxicity, genotoxicity and oxidative stress induced in vitro by DOX. The genoprotective effect of ARA290 on DOX-induced toxicity in three cell line (HepG2, HGF & Stem cell) were assessed. Cells were treated with ARA290 (50–400 nM) and DOX (1 μM) in pretreatment condition. Cytotoxicity was evaluated using the MTT assay, genoprotective effect of ARA290 were evaluated using the micronucleus test and comet assay. AR290 significantly reduced the percentage of DNA in tail and the frequency of micronuclei induced by DOX. Besides, DOX impaired anti-oxidant defense enzyme activities and induced inflammation and apoptotic cell death. ARA290 markedly attenuated DOX induced oxidative stress and protected against DOX induced inflammation and apoptotic cell death. This result proposes that ARA290 can act as a protective agent, reducing DOX-induced DNA damage and oxidative stress, and it is possible that this protection could also extend to cardiac cells. Highlights: ARA290 showed genoprotective effect on different cells exposed to doxorubicin. The genoprotective effect of ARA290 was confirmed by alkaline comet assay and Micronucleus assay. The antigenotoxic, antioxidant, anti-inflammation and anti-apoptotic properties of ARA290 are indicated. The genoprotective effect of the ARA290 is concentration-dependant. Several mechanisms contributing to its protective action are proposed.